Sistem Pendukung Keputusan Penerima Bantuan Langsung Tunai Dana Desa (BLT-DD) Menggunakan Algoritma Preference Selection Index (PSI) - Tampubolon, Putri Tasya Agustina; Chairani, T.Sofia; Niska, Debi Yandra (Infotek: Jurnal Informatika dan Teknologi, 2025)
The Village Fund Direct Cash Assistance (BLT-DD) program is one of the government's efforts to help poor families in the village. However, the recipient selection process is still done manually through deliberations of village officials, making it prone to mistargeting and lack of transparency. This research aims to build a Decision Support System (SPK) that is able to determine prospective BLT-DD recipients objectively and efficiently. The method used is the Preference Selection Index (PSI), which can solve multicriteria decision-making problems without the need to assign weights between criteria. The five main criteria used include welfare decile, health status, program participation, marital status, and gender of the family head. Testing was conducted on 10 alternative data. The calculation results show that alternative A3 has the highest score of 1.66. This system is able to improve accuracy, efficiency, and transparency in BLT-DD distribution.